2003
DOI: 10.1007/s11916-003-0047-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in malignant bowel obstruction: an interface of old and new

Abstract: Malignant bowel obstruction continues to be a difficult problem for patients with abdominal and pelvic primary tumors and tumors originating in other sites. The main treatment options consist of surgery, stenting, and pharmacotherapy. Despite recent advances, the impact of available treatment modalities on symptom control, longevity, quality of life, and associated health care costs have not been evaluated rigorously. This article reviews the available data and suggests an approach to the management of this ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Octreotide, a synthetic analog of somatostatin, is administered to manage the symptoms of bowel obstruction and inhibits the release of several gastrointestinal hormones, thereby modulating gastrointestinal functions by reducing gastric and intestinal secretions, slowing down intestinal motility, decreasing bile flow, and increasing the absorption of water and electrolytes thereby reducing bowel distension and vomiting [4,15]. A randomized controlled study, comparing Octreotide with hyoscyamine, scopolamine butylbromide, and opioid demonstrated a statistically significant improvement in nausea, vomiting, and anorexia in the Octreotide group [16].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…Octreotide, a synthetic analog of somatostatin, is administered to manage the symptoms of bowel obstruction and inhibits the release of several gastrointestinal hormones, thereby modulating gastrointestinal functions by reducing gastric and intestinal secretions, slowing down intestinal motility, decreasing bile flow, and increasing the absorption of water and electrolytes thereby reducing bowel distension and vomiting [4,15]. A randomized controlled study, comparing Octreotide with hyoscyamine, scopolamine butylbromide, and opioid demonstrated a statistically significant improvement in nausea, vomiting, and anorexia in the Octreotide group [16].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…Preoperative nasogastric intubation and intravenous fluid and electrolyte resuscitation is necessary. The value of conservative treatment as the only method of treating malignant obstruction is questionable [2,3]. Variable primary pathology recommended different surgical strategy and adjuvant treatment in the patients studied.…”
Section: Discussionmentioning
confidence: 99%
“…At operation, locally advanced pelvic tumours, occasionally arising from the uterus and internal genitalia, can be removed en bloc with the rectum and sigmoid colon [1,2]. This procedure was deemed necessary in a selected group of 12 patients presenting with acute malignant bowel obstruction of unknown origin.…”
Section: Introductionmentioning
confidence: 99%
“…Anticholinergics (hyoscine, scopolamine, glycopyrrolate) are used to slow peristaltic contractions. [6][7][8] Antisecretory drugs include thesomatostatin analogue (octreotide). 2,7,8 Antiemetics used include dopamine antagonists (haloperidol, metoclopramide, chlorpromazine), serotonin antagonist (ondansetron, granisetron) and steroids (dexamethasone).…”
Section: Managementmentioning
confidence: 99%
“…[6][7][8] Antisecretory drugs include thesomatostatin analogue (octreotide). 2,7,8 Antiemetics used include dopamine antagonists (haloperidol, metoclopramide, chlorpromazine), serotonin antagonist (ondansetron, granisetron) and steroids (dexamethasone). 2,7,8 The appropriate and timely medical management of MBO provides spontaneous resolution in more than one-third of patients.…”
Section: Managementmentioning
confidence: 99%